2012
DOI: 10.1210/me.2011-1258
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: Identification of Novel Growth Hormone-Regulated Phosphorylation Sites by Quantitative Phosphoproteomics

Abstract: GH and GH receptors are expressed throughout life, and GH elicits a diverse range of responses, including growth and altered metabolism. It is therefore important to understand the full spectrum of GH signaling pathways and cellular responses. We applied mass spectrometry-based phosphoproteomics combined with stable isotope labeling with amino acids in cell culture to identify proteins rapidly phosphorylated in response to GH in 3T3-F442A preadipocytes. We identified 132 phosphosites in 95 proteins that exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
0
10
0
1
Order By: Relevance
“…ATM can be regulated via different pathways. After DNA damage, the Mre11/Rad50/Nbs1 (MRN) DNA-binding complex is required for ATM activation (87), and spectrometry-based phosphoproteomics showed that GH rapidly dephosphorylates Mre11 and Rad50 in 3T3-F442A preadipocytes, potentially affecting activity of the MRN complex (88). TRIM29, induced by DNA damage, binds and degrades the histone acetyltransferase Tip60 (46), which also induces ATM kinase activity in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…ATM can be regulated via different pathways. After DNA damage, the Mre11/Rad50/Nbs1 (MRN) DNA-binding complex is required for ATM activation (87), and spectrometry-based phosphoproteomics showed that GH rapidly dephosphorylates Mre11 and Rad50 in 3T3-F442A preadipocytes, potentially affecting activity of the MRN complex (88). TRIM29, induced by DNA damage, binds and degrades the histone acetyltransferase Tip60 (46), which also induces ATM kinase activity in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal control of phosphorylation events due to an imbalance of kinase and phosphatase activities has been linked to a large number of disease states, including cancer (36), diabetes (7, 8), and Alzheimer’s disease (911). Phosphorylation is a central process in signal transduction to activate and propagate signals through phosphorylation cascades in response to specific stimuli such as hormones, growth factors, and drugs (1, 12, 13). In addition, phosphorylation has a broad range of effects on target proteins, including control of subcellular localization, protein structure, protein interactions, and enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…These direct effects of phosphorylation on protein function make quantitative phosphoproteome analysis useful for identifying and characterizing changes in protein function and for mapping control pathways. The use of quantitative phosphoproteome analysis in conjunction with time course studies (1, 12, 14) and genetic interventions (1, 15), are particularly useful in deciphering signal transduction pathways and provide direct insights into many biological processes (1626). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations